Content analysis of Australian direct‐to‐consumer websites for emerging breast cancer imaging devices. Issue 5 (1st September 2014) - Vreugdenburg, Thomas D; Laurence, Caroline O; Willis, Cameron D; Mundy, Linda; Hiller, Janet E
Abstract: Objective: To describe the nature and frequency of information presented on direct‐to‐consumer websites for emerging breast cancer imaging devices. Design: Content analysis of Australian website advertisements from 2 March 2011 to 30 March 2012, for three emerging breast cancer imaging devices: digital infrared thermal imaging, electrical impedance scanning and electronic palpation imaging. Main outcome measures: Type of imaging offered, device safety, device performance, application of device, target population, supporting evidence and comparator tests. Results: Thirty‐nine unique Australian websites promoting a direct‐to‐consumer breast imaging device were identified. Despite a lack of supporting evidence, 22 websites advertised devices for diagnosis, 20 advertised devices for screening, 13 advertised devices for prevention and 13 advertised devices for identifying breast cancer risk factors. Similarly, advertised ranges of diagnostic sensitivity (78%–99%) and specificity (44%–91%) were relatively high compared with published literature. Direct comparisons with conventional screening tools that favoured the new device were highly prominent (31 websites), and one‐third of websites (12) explicitly promoted their device as a suitable alternative. Conclusions: Australian websites for emerging breast imaging devices, which are also available internationally, promote the use of such devices as safe and effective solutions for breast cancer screening and diagnosis in a range of target populations. Many of these claims are not supported by peer‐reviewed evidence, raising questions about the manner in which these devices and their advertising material are regulated, particularly when they are promoted as direct alternatives to established screening interventions.